Potential target and mechanism exploration from α-mangostin against triple-negative breast cancer: An in silico study - Rafly Mochamad Rivaldo; Paulus Chandra (Wolters Kluwer Medknow Publications, 2024)
Triple-negative breast cancer (TNBC) is one of the most common types of serious breast cancer. Due to the absence of therapeutic hormone receptors, TNBC treatment generally involves chemotherapy which results in various side effects and resistance development. Herbal compounds, including α-mangostin, have shown potential anticancer effects against TNBC. However, rigorous screening is needed to uncover its mechanisms and characteristics. The aim of this study was to understand the molecular mechanism of α-mangostin against TNBC and its possible limitations. The study design used is an in silico study. The study involved database mining and compound characteristic analysis. Network pharmacology and molecular docking were also done to explore potential target and molecular mechanisms against TNBC. There was no statistical analysis conducted as this study relies on predefined algorithms and simulation models. Instead, a parameter threshold was used for each analysis to ensure its reliability. Prediction of Activity Spectra for Substances prediction and Gene Ontology-Kyoto Encyclopedia of Genes and Genomes enrichment predicted potential anticancer effects of α-mangostin through the regulation of enzyme activity and apoptotic pathway. Compound property predictions showed α-mangostin to have promising drug-likeness with sufficient bioavailability and low biodegradability. However, α-mangostin still has some potential limitations in water solubility and toxicity risks. Through network pharmacology, 75 potential target proteins of α-mangostin in TNBC cases were found. The top three most significant of which (AKT1, CTNNB1, and HSPAA91) were proven to bind with α-mangostin through molecular docking. Study results suggested α-mangostin to have a promising anticancer and chemopreventive activity with great drug-likeness and pharmacokinetic properties. It was revealed that α-mangostin can bind to key components in TNBC-related pathways, including AKT1, CTNNB1, and HSP90AA1 proteins. However, further experimental studies may be needed to verify its effectiveness as well as possible solubility and toxicity limitations.